Preparation of Financial Reports for UMKM Zulfan Olshop Based on Excel for Accounting - Yulyanah, Yulyanah; Romenah, Romenah; Oktaviani, Ega (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
This research aims to find out how the recording system created by Zulfan Olshop is and to assist in the process of preparing financial reports using Microsoft Excel for Accounting (EFA). This research uses field observation methods, interviews and a simple Excel system. The analysis method used is a qualitative descriptive approach. The output of the research is that MSMEs can have the ability to make financial reports using Microsoft Excel, where initially the Accountant still manually prepares financial reports, then they can use Microsoft Excel for Accounting (EFA) which adapts to EMKM's SAK. The preparation of financial reports using Microsoft Excel for Accounting (EFA) is made according to Zulfan Olshop's needs in the hope that it can help and provide positive results for his business in carrying out financial reports using Microsoft Excel for Accounting (EFA).